Moral Education based on Pancasila: Reaffirming Pancasila as the Philosophical foundation of moral Education in Indonesia - Husnul Fatihah; Dasim Budimansyah; Sapriya; Dadi Mulyati; Mirwan Fikri Muhkam; Ronni Juwandi; Rio Razab Isdendi (Sriwijaya University Learning and Education International Journal, 2025)
As social beings, humans need morals to organize their lives for the better. Morals can be shaped through parental upbringing and education at school. The formation of morals in each individual is not merely a rational act, but aims to develop human behavior that is conscious of ethics, empathy, and wisdom. One way to shape morals is through moral education aimed at the general public and academics. To develop such morality, Pancasila is used as a foundation. The implementation of moral education based on Pancasila, as emphasized in this study, is achieved through various means such as curriculum, extracurricular activities, learning models, teacher role modeling, and parental role modeling. The values of Pancasila serve as a strong foundation in shaping the morality of the younger generation in today's digital era. Referring to the literature, this article is expected to serve as a reference for universities, schools, and organizations discussing moral education in line with the practice of Pancasila values. For universities, moral education based on Pancasila serves as a platform for developing noble character. For schools, moral education based on Pancasila helps students develop the ability to process emotions and thoughts to distinguish between what is good and what is bad. For organizations, moral education based on Pancasila strengthens understanding of integrity, ethics, and good governance within an organizational context.